Adipokines Regulate the Expression of Tumor-Relevant MicroRNAs - Jasinski-Bergner, Simon (Obes Facts, 2019)
BACKGROUND: Increasing prevalence of obesity requires the investigation of respective comorbidities, including tumor diseases like colorectal, renal, post-menopausal breast, prostate cancer, and leukemia. To date, molecular mechanisms of the malignant transformation of these peripheral tissues induced by obesity remain unclear. Adipose tissue secretes factors with hormone-like functions, the adipokines, and is therefore categorized as an endocrine organ. Current research demonstrates the ability of adipose tissue to alter DNA methylation and gene expression in peripheral tissues, probably affecting microRNA (miR) expression. METHODS: Literature was analyzed for adipokine-regulated miRs. Many of these adipokine upregulated or downregulated miRs exert either oncogenic or anti-tumoral potential. RESULTS: The three selected and analyzed adipokines, adiponectin, leptin, and resistin, induce more strongly oncogenic miRs and simultaneously reduce anti-tumoral miRs than vice versa. This effect is not only true for the pure number of regulated miRs, it is also the case by consideration of the abundance of the respective miR expression based on actual data sets derived from next-generation sequencing. CONCLUSION: The link of obesity and cancer is analyzed under the aspect of adipokine-regulated miRs. At the same time the impact of miR abundance is considered as a regulatory variable. This context offers new strategies for tumor therapy and diagnostics.